A process inspired by fractals for embedding digital codes into additively manufactured components for supply chain security - Saber Nemati; Ali Mahmoudi; Kyungmin Ham; Tie Siemers; Shengmin Guo; Josephine Gutekunst; Joachim Schulz; Ian Taylor; Michele Maasberg; Leslie G. Butler (Scientific Reports)
Abstract This study describes procedures for embedding digital information into additively manufactured components as well as procedures for readout and tensile testing. Embedded digital codes were printed inside ASTM E8/E8M dumbbells using Direct Metal Laser Melting (DMLS) with an EOS M290 printer. The codes were configured as either ellipsoids or prolate spheroids in patterns given by the Cantor dust fractal. Tensile testing was performed on 15 dumbbells, 7 with digital codes in the gauge volume and 8 with codes in the dumbbell tail. Results showed that the dumbbells met the ultimate tensile strength specification for the EOS AlF357 powder. X-ray imaging, both conventional and interferometry, was explored to detect the digital information. X-ray tomography showed measured ellipsoid volumes slightly larger than as-designed ellipsoid volumes, even when partially filled with loose powder. X-ray interferometry showed increased void detectability, one advantage of loose powder. These results suggest a standard selective laser sintering printer with typical metal powders could reasonably expect to print 100 bits of embedded digital information in a gauge volume 6 mm in diameter as 300  $$\upmu$$ m voids while still maintaining tensile specifications.